THE EFFECT OF FINANCIAL DERIVATIVES AND THIN CAPITALIZATION ON TAX AVOIDANCE PRACTICES - Amirah ‘Aliyah Al Ya’qubi; Nyimas Wardatul Afiqoh (Proceeding of International Conference on Social Science and Humanity, 2026)
Objective: This study aims to examine the effect of financial derivatives and thin capitalization on tax avoidance in companies listed on the Indonesia Stock Exchange. Method: The study used a quantitative approach with secondary data from annual financial reports and generated 60 companies through purposive sampling. The analysis was conducted using multiple linear regression. Results: The results show that financial derivatives have no significant effect on tax avoidance, while thin capitalization has a significant positive effect on tax avoidance. Simultaneously, both variables influence tax avoidance. Novelty: These findings suggest that capital structure, particularly the use of debt, is an important factor in corporate tax avoidance practices.